Lohnimpulse und Wirtschaftswachstum — eine Simulationsanalyse für die Eurozone - Jan Limbers; Thieß Petersen; Michael Böhmer (Wirtschaftsdienst, 2016)
Seit der globalen Finanz- und Wirtschaftskrise und der sich daran anschließenden Staatsschuldenkrise stellt sich die Frage, ob die Krisenländer durch eine Verbesserung ihrer internationalen preislichen Wettbewerbsfähigkeit auf einen stabilen Wachstumspfad zurückkehren können, z.B. durch Lohnzurückhaltung. Anhand von Simulationsrechnungen für unterschiedliche Lohnsetzungsstrategien auf europäischer Ebene bis 2030 werden deren Vor- und Nachteile diskutiert. – – Since the global financial and economic crisis, the question has arisen whether a policy of wage restraint could lead the European crisis countries back onto a more stable growth path. Using simulation calculations for varying wage setting strategies in Europe through 2030, the advantages and disadvantages of such a scenario can be discussed. One of the main fi ndings is that temporary wage restraint in the economically weak countries only works as a means to regaining competitiveness if accompanied by other economic policies at the European level. These policies include higher wage growth in the economically stronger countries, transfer payments to foster investments and the acceptance of higher inflation rates in the eurozone.
Keywords: C15; F45; J30; 330; Lohnpolitik; Wirtschaftswachstum; Wirkungsanalyse; Simulation; Eurozone